Synthesis and characterization of Fe(II),Co(II),Ni(II),Cu(II) and Zn(II) complexes with Hexaaza macromolecule Ligands Derived from Semicarbazide - Saad Dawood; Falah Fakhree (College of Education for Pure Sciences, 2013)
ABSTRACT A new ligands( 3,4,6,14,15,17,23,24-Octaazatricyclo [17.3.1.18,12] tetracosa-1(23),8(24),9,11, 19 ,21- hexaene - 2,5,7,13,16,18 - hexaone), (L1) and 2-(5-hydroxypentanoyl) hydrazinecarboxamide,(L2)was prepared from the reaction of pyridine-2,6-dicarboxylic acid and glutaric acid with semicarbazide by microwave irradiation in solid state ,then was  reacted  with some transition metal(II) ions to form complexes of the type   [M(L1)Cl2] , [M(L1)]Cl2 and [M(L2)2 Cl]Cl , [M(L2)2Cl2]where M= Fe(II) ,Co(II),Ni(II),Cu(II) and Zn(II). Adducts of  the type  [M(L1)(PPh3)Cl]Cl, [M(L2)2(PPh3)]Cl2 and [M(L2)2(PPh3)Cl]Cl were prepared by the reaction of  the above complexes with triphenylphosphine in a  2:1 and 1:1 molar ratio . The prepared complexes and adducts were characterized by (C,H,N) analysis , metal content analysis , molar conductance, magnetic moment  measurements ,electronic and  IR spectroscopy, the ligand was characterized by 1H,13C -NMR . The electronic spectra and magnetic measurements indicated that the complexes have octahedral environment around the metal ions.